Stochastic Semigroups and Coagulation Equations - Lachowicz, M. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
A general class of bilinear systems of discrete or continuous coagulation equations is considered. It is shown that their solutions can be approximated by the solutions of appropriate stochastic systems describing the coagulation process in terms of stochastic semigroups.